Increasing The Growth And Production Of Sweet Corn (Zea mays saccharata) by Giving Chicken Manure And Vegetable Waste Liquid Organic Fertilizer - Novia Septiani Sinaga; Devi Andriani Luta; Ruth Riah Ate Tarigan (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2023)
Applying organic fertilizers can improve the physical and biological properties of the soil. One of the organic fertilizers that can be used is chicken manure with the addition of POC vegetable waste. This study aims to determine the effectiveness of applying organic chicken manure and POC vegetable waste on the growth and production of sweet corn (Zea mays Saccharata). This study used a factorial randomized block design (RBD) consisting of 2 factors with 16 combinations and 3 blocks. The first factor is the application of organic chicken manure (A), which consists of 4 levels. 0 g/plot, 700 g/plot, 1400 g/plot, 2100 g/plot. The second factor is the provision of POC of vegetable waste (S) which consists of 4 levels, namely, 0 ml/liter of water/plot, 300 ml/liter of water/plot, 500 ml/liter of water/plot, 700 ml/liter of water/plot.The parameters observed were plant height (cm), number of leaves (strands), cob length (cm), cob diameter (cm) and production weight using klobot per plot (g). The results showed that the application of organic chicken manure had a significant effect on Production weight parameters used husks per plot (g) and had no significant effect on plant height (cm), number of leaves (strands), cob length (cm) and cob diameter (cm).